Particle transport due to energetic-particle-driven geodesic acoustic modes. (29th August 2018) - Zarzoso, D.; del-Castillo-Negrete, D.; Escande, D.F.; Sarazin, Y.; Garbet, X.; Grandgirard, V.; Passeron, C.; Latu, G.; Benkadda, S.
Abstract: The transport of particles in the presence of energetic geodesic acoustic modes (EGAMs) is analysed by means of full- f global gyro-kinetic simulations, using the multi-species version of the code and a test particle tracking post-treatment, which solves the equations of motion of passive gyro-centres embedded in the self-consistent EGAM potential obtained from the simulations. It is found that EGAMs induce the transport of particles, which eventually results in counter-passing particle losses modulated at the EGAM frequency. A detailed analysis of the trajectories of the test gyro-centres is performed and evidence of the interaction between the EGAM island and the region of magnetically trapped particles (trapping cone) is provided. In particular, we report for the first time on the complex interaction between the stochastic separatrix of the EGAM island and the X-point of the trapping cone, creating a channel for the transport of particles from the to the regions. Therefore, for the cases analysed in this work, the co-injection of energetic particles might lead to a significant reduction of EGAM-induced losses. This result opens up new perspectives for further studies of the selection of energetic particle injection in order to minimize the losses due to EGAMs.